Learning in school-university partnership [ sociocultural perspectives - Tsui, Amy; Edwards, Gwyn; Kwan, Tammy; Lopez-Real, Francis J. (Routledge, 2009)
Looks at school-university partnerships from sociocultural perspectives of learning that view participation in social practice as fundamental to the process of learning. This volume considers two